2015
DOI: 10.3389/fpsyg.2015.00698
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the music therapy assessment tool for awareness in disorders of consciousness (MATADOC) for use with pediatric populations

Abstract: Measuring responsiveness to gain accurate diagnosis in populations with disorders of consciousness (DOC) is of central concern because these patients have such complex clinical presentations. Due to the uncertainty of accuracy for both behavioral and neurophysiological measures in DOC, combined assessment approaches are recommended. A number of standardized behavioral measures can be used with adults with DOC with minor to moderate reservations relating to the measures’ psychometric properties and clinical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…12 Exploring its utility for children with DOC, a pilot study indicated that the MATADOC provided a useful protocol and measure for behavioural assessment and clinical treatment planning with paediatric DOC. 6 Musical stimuli produced responses in the visual and auditory domains suggestive of higher-level functioning when compared with other DOC measures. This suggests that musical stimuli might be effective in maximising the potential to demonstrate awareness and assess consciousness in children and young people with DOC.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…12 Exploring its utility for children with DOC, a pilot study indicated that the MATADOC provided a useful protocol and measure for behavioural assessment and clinical treatment planning with paediatric DOC. 6 Musical stimuli produced responses in the visual and auditory domains suggestive of higher-level functioning when compared with other DOC measures. This suggests that musical stimuli might be effective in maximising the potential to demonstrate awareness and assess consciousness in children and young people with DOC.…”
Section: Introductionmentioning
confidence: 94%
“…3 4 Consequently, there is a lack of research with this population, 5 in part because no DOC measures have been validated specifically for use with children. 6 Further research on this complex population is required to improve our understanding of prognosis and recovery, to address concerns regarding accurate diagnosis and to develop appropriate treatments. 5 Language-based assessments and interventions with DOC are not the most appropriate for stimulating optimal responsiveness as the severity of brain damage incurred typically results in language disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of the described tools emerged from the previous analysis of literature that points out the lack of validated observational instruments to consistently evaluate the MT process. In fact, although some instruments measure cognitive, sensory, or motor variables (Jeong & Lesiuk, 2011;Lipe, 1995;Lipe et al, 2007;Magee, 2007;Magee et al, 2013Magee et al, , 2015Magee et al, , 2016O'Kelly & Bodak, 2016;Sutton, 1984), most of them evaluate client's aptitude in terms of communication, social behaviour, musical expression, or engagement in musical activity (Bell et al, 2014;Clair et al, 2005;Layman et al, 2002;McDermott et al, 2014McDermott et al, , 2015O'Kelly & Bodak, 2016;von Moreau, 1996;von Moreau et al, 2010;Wasserman et al, 1973). Only one tool takes into account behaviours indicating the client-therapist relationship in improvisational MT (Mahoney, 2010;Nordoff & Robbins, 1977).…”
Section: O1548mentioning
confidence: 99%
“…This tool is based on client observation during a 15‐min group protocol including rhythmic playing, physical exercises with music, and familiar song singing (5 min each). The Music Therapy Assessment tool for Awareness in Disorders of Consciousness (Magee, ; Magee et al, , , ) is a diagnostic, initial assessment, and outcome measure developed for adults with disorders of consciousness and later extended to the paediatric population. The scale measures motor responses, communication, arousal, and auditory and visual responsiveness during a MT assessment where the client is asked to perform a series of different tasks.…”
Section: Introductionmentioning
confidence: 99%